2016
DOI: 10.1016/j.neuropharm.2016.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Stress increases GABAergic neurotransmission in CRF neurons of the central amygdala and bed nucleus stria terminalis

Abstract: Corticotrophin Releasing Factor (CRF) is a critical stress-related neuropeptide in major output pathways of the amygdala, including the central nucleus (CeA), and in a key projection target of the CeA, the bed nucleus of the stria terminalis (BnST). While progress has been made in understanding the contributions and characteristics of CRF as a neuropeptide in rodent behavior, little attention has been committed to determine the properties and synaptic physiology of specific populations of CRF-expressing (CRF(+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 77 publications
5
67
1
Order By: Relevance
“…However, its influence on the distribution of sIPSC amplitude was significant in these cells, reflecting increases in the fraction of sIPSCs with larger amplitudes. Actually, several earlier studies have found that acute stress enhanced the efflux of GABA in BA [29] and its neighboring central amygdala [30]. Thus, acute stress also recruits the inhibitory network in BA.…”
Section: Discussionmentioning
confidence: 97%
“…However, its influence on the distribution of sIPSC amplitude was significant in these cells, reflecting increases in the fraction of sIPSCs with larger amplitudes. Actually, several earlier studies have found that acute stress enhanced the efflux of GABA in BA [29] and its neighboring central amygdala [30]. Thus, acute stress also recruits the inhibitory network in BA.…”
Section: Discussionmentioning
confidence: 97%
“…Rouwette et al suggest that changes of CRF1 and CRF2 receptors expression in the CeAmy could underlie neuropathic pain [22]. A very recent paper demonstrated that chronic unpredictable stress alters the GABA neurotransmission between amygdala CRF neurons and inhibits CeAmy output to BNST [13]. It is plausible that persistent pain causes similar changes in CeAmy output that lead to inhibition of descending pain modulation and more specifically to inhibition of LC activity.…”
Section: Discussionmentioning
confidence: 99%
“…The CeAmy is a key element in descending inhibition of pain and is essential for robust SIA [11]. The projections of the CeAmy target the bed nucleus of stria terminalis (BNST) and several brainstem nuclei, including the LC [12, 13]. There is general agreement that CeAmy CRF neurons do not affect baseline sensory thresholds but their role in pain is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The peptide can be synthesized and stored at specific GABAergic and glutamatergic synapses (Cain et al, 1991; Valentino et al, 2001a; Valentino et al, 2001b), and is usually co-released with classical neurotransmitters (Partridge et al, 2016) in response to neuronal firing to modulate their synaptic effects (Rainnie et al, 1992; Yu and Shinnick-Gallagher, 1998). The CRF system can produce a variety of region-, cell type- and synapse-specific effects depending on the distribution of its signaling elements within local and regional circuits (Henckens et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%